Calidad de servicio y satisfacción del cliente de la Empresa de Telefonía Macga, Iquitos 2022 - Garcia Navarro, Andres (2023)
The objective of this research is to determine the relationship between the quality of service and customer satisfaction in the telephone company MACGA, Iquitos 2022. The type of correlational descriptive research was used, it has a sample of 50 customers. Pearson's correlation is equal to 0.647, which indicates a high correlation, the sigma value (bilateral) is 0.000; the calculated p-value is = 0.05. But, if the calculated p-value is less than 0.05, Ha will be accepted. According to the value obtained, we confirm that the alternative hypothesis is accepted; then, it was concluded that the hypothesis is accepted, which shows us that the relationship is high between the two study variables.